27.1k views
3 votes
If f(x) = 2x + 5x and g(x) = 3x — 5, find (f+ g)(x).

If f(x) = 2x + 5x and g(x) = 3x — 5, find (f+ g)(x).-example-1

2 Answers

3 votes

Given:

f(x) = 2^x + 5x

g(x) = 3x - 5

To Find:

( f + g ) ( x ) = f(x) + g(x)

Step-by-step explanation:

By putting the values, we get

2^x + 5x + 3x - 5

= 2^x + 8x - 5

Answer:

(f+g)(x) = 2^x + 8x - 5

User Vladimir Kroz
by
4.9k points
1 vote

Answer:

  • 2^x + 8x - 5

Step-by-step explanation:

Given

  • f(x) = 2^x + 5x and g(x) = 3x - 5

To find

  • (f+ g)(x)

Solution

  • (f+ g)(x) =
  • f(x) + g(x) =
  • 2^x + 5x + 3x - 5 =
  • 2^x + 8x - 5
User Yuriy Rozhovetskiy
by
5.1k points